Effect of sintering temperatures on the physical, structural properties and microstructure of mullite-based ceramics - Jalaluddin, Mohamed Lokman; Umar Al-Amani Azlan, Umar Al-Amani Azlan; Abd Rashid, Mohd Warikh; Tamin, Norfauzi (2024)
This study explored the impact of sintering temperature variations on the synthesis and characteristics of mullite ceramics derived from a composite blend of kaolinite clay, silica (silicon dioxide), and feldspar. Sintering temperatures ranging from 1100 to 1200 °C were systematically examined to analyze alterations in shrinkage, density, microstructure, elemental composition, and phase formation. The study revealed that an increase in sintering temperature led to decreased shrinkage due to improved particle packing and reduced porosity. Ceramic density showed a direct relation with sintering temperature, reaching the optimal density at 1175 °C and indicating efficient particle packing and compaction. Analysis through field emission scanning electron microscopy (FESEM) provided insights into microstructural changes, including alterations in grain morphology, porosity, and connectivity. Energy dispersive X-ray spectroscopy (EDS) clarified element distribution within the microstructure, offering valuable information on compositional variations. X-ray diffraction (XRD) examinations unveiled temperature-dependent phase transformations, which confirmed the successful formation of mullite during the sintering process. A sintering temperature of 1175 °C yielded the optimal ceramic quality and cost-effectiveness for high-temperature heating processes.